Comparative effectiveness and cost of adding rituximab to first-line chemotherapy for elderly patients diagnosed with diffuse large B-cell lymphoma - Griffiths, R; Gleeson, M; Mikhael, J; Dreyling, M; Danese, MD (2012)
BACKGROUND: Clinical trials indicate that rituximab improves the survival of patients with diffuse large B-cell lymphoma (DLBCL). Economic models using multiple data sources, including clinical trials for survival outcomes, have projected cost offsets/savings and favorable cost-effectiveness associated with rituximab. In this study, the authors evaluated survival and cost impacts of adding rituximab to first-line chemotherapy for DLBCL using a single database that reflects routine clinical practice among elderly patients in the United States. METHODS: By using Surveillance, Epidemiology, and End Results (SEER) data linked to Medicare, the authors identified 5484 elderly patients who were diagnosed with DLBCL between January 1999 and December 2005 who had claims through December 2007. Included patients began chemotherapy with or without rituximab within 180 days of diagnosis. Multivariate analyses were conducted to estimate the impact of rituximab on mortality and costs to Medicare. The cost per life-year gained of rituximab was calculated using cost and survival estimates from the multivariate analyses. RESULTS: The mean patient age was 76 years, 43% of patients had stage III or IV disease, and 64% received rituximab. In a Cox regression model, rituximab resulted in lower 4-year all-cause mortality (hazard ratio [HR], 0.68; 95% confidence interval [CI], 0.61-0.74) and cancer mortality, and the incremental cumulative survival was 0.37 years. In least-squares regression, rituximab resulted in higher 4-year total costs ($23,097; 95% CI, $19,129-$27,298), immunochemotherapy costs ($12,069; 95% CI, $10,687-$13,634), other cancer costs ($7655; 95% CI, $5067-$10,489), and noncancer costs ($3461; 95% CI, $1319-$5650). The cost per life-year gained was $62,424. CONCLUSIONS: In routine clinical practice, rituximab was associated with survival benefits comparable to those observed in clinical trials. However, these benefits did not translate into the previously reported cost savings. © 2012 American Cancer Society.